Glycemic index, glycemic load and carbohydrate intake in association with risk of renal cell carcinoma - Zhu, Jingfen (Carcinogenesis, 2017)
Carbohydrate intake affects postprandial glucose levels and insulin response, which plays a role in carcinogenesis. The relationship between carbohydrate intake, dietary glycemic index (GI) and glycemic load (GL), and risk of renal cell carcinoma (RCC) remains unclear. We conducted a case–control study including 854 patients with newly diagnosed RCC (cases) and 1255 healthy participants (controls) recruited since 2002. GI, GL and carbohydrate intake were obtained via a validated food frequency questionnaire. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using multivariable logistic regression, adjusting for potential confounders. We found that higher GI was significantly associated with RCC risk with an OR of 1.32 (95% CI, 0.99–1.74; P(trend) = 0.026) (the highest versus the lowest quartiles). We also observed an inverse association between fiber intake and RCC risk with OR of 0.70 (95% CI = 0.50–0.99) as well as between starch intake and risk of RCC with OR of 0.65 (95% CI = 0.49–0.87). Individuals with a high-GI diet and hypertension or high body mass index (BMI) had a 2.7 times (OR = 2.67, 95% CI = 1.96–3.64) and two times (OR = 1.95, 95% CI = 1.29–2.92) higher RCC risk, respectively, than those without these factors. Our findings suggest that a high-GI diet is associated with an increased risk of RCC, whereas increased fiber and starch intakes appear to be associated with a decreased risk of RCC. We found that reducing GI levels and increasing fiber intake could be a dietary strategy to decrease RCC risk, especially for individuals with hypertension or high BMI.